Understanding summertime H2O2 chemistry in the North China Plain through observations and modeling studies - C. Ye; P. Liu; C. Xue; C. Zhang; Z. Ma; C. Liu; J. Liu; K. Lu; Y. Mu; Y. Zhang (Atmospheric Chemistry and Physics, 2025)
Hydrogen peroxide (H2O2) is a key atmospheric oxidant, crucial for oxidation capacity and sulfate production. However, its chemistry remains understudied compared to ozone (O3), limiting our understanding of photochemical pollution. In summer 2016, atmospheric peroxides and trace gases were measured at a rural site in the North China Plain. H2O2 was the dominant peroxide (0.62 ± 0.80 ppb), constituting 69 % of total peroxides. It exhibited diurnal variation similar to peroxyacetyl nitrate (PAN) and O3, indicating photochemical production. The O3<mspace width="0.125em" linebreak="nobreak"/>/<mspace linebreak="nobreak" width="0.125em"/>H2O2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="50pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="06902578fea60196e9a44a2af6762aaa"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6991-2025-ie00001.svg" width="50pt" height="14pt" src="acp-25-6991-2025-ie00001.png"/></svg:svg> ratio was higher on high-particle days, suggesting that H2O2 uptake by particles reduces its concentration. A box model with default gas-phase chemistry overestimated H2O2 by a factor of 2.7, and including particle uptake of H2O2 (uptake coefficient of 6 × 10−4) improved agreement with observations, although we note that this value carries some uncertainty related to the assumed HO2 uptake coefficient.